Nitric oxide: News from stem cells to platelets - D'Atri, Lina Paola (1997)
Nitric oxide (NO) is a diffusible, short-lived, diatomic free radical ubiquitously produced by mammalian cells. The generation of NO from L-arginine is enzymatically regulated by three different isoforms of NO synthases. The NO signaling pathway involves mainly the activation of soluble guanylyl cyclase to produce cyclic GMP (cGMP) as a second messenger and downstream mediator. In addition, the free radical activity of NO can cause cellular damage through a phenomenon known as nitrosative stress. NO is a pleiotropic biomodulator in several systems, including the cardiovascular, nervous and immune systems. In the hematopoietic system, NO is thought to be an autocrine or paracrine messenger but also an intracellular effector molecule. Megakaryopoiesis and subsequent thrombopoiesis occur through complex biologic steps that involve hematopoietic stem cell commitment to megakaryocytic lineage, megakaryocyte maturation and finally, platelet release. Here, we summarize the current knowledge regarding the role of exogenous and endogenous NO in hematopoietic stem cell biology, megakaryocyte development and platelet biogenesis as well as relevance of platelet-derived NO generation on platelet function. Dysregulation of NO synthesis has been observed in several diseases, and the evaluation of a series of pharmacological agents with the ability to modulate the NO/ cGMP pathway in platelets will also be discussed.